2010
DOI: 10.1073/pnas.1004185107
|View full text |Cite
|
Sign up to set email alerts
|

Leptin signaling maintains B-cell homeostasis via induction of Bcl-2 and Cyclin D1

Abstract: Regulation of apoptosis and cell cycle progression plays an essential role in the maintenance of B-cell homeostasis, because a fine balance of survival and expansion is critical for preventing lymphocytic disorders. Although remarkable progress in understanding B-cell development has been achieved, much less is known concerning niches that are critical to the maintenance of B-cell homeostasis. Leptin has recently been recognized to be important for modulating the immune responses, but it has remained unclear h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 24 publications
(29 reference statements)
2
67
1
1
Order By: Relevance
“…These results are supported by previous studies that demonstrated that similar daily administrations with leptin reduce the incidence of follicular apoptosis after 7 days of leptin injection and that leptin may be involved in accelerating follicular maturation by attenuating follicular atresia through an increase in the BCL2/BAX ratio (Almog et al 2001). In addition, using different in vitro systems, other authors have found that leptin reduces apoptosis and induces cell proliferation, at least in part, by upregulating BCL2 expression (Brown & Dunmore 2007, Sirotkin & Grossmann 2007, Lam et al 2010, and that leptin may act as an anti-apoptotic factor in luteinized porcine granulosa cells by increasing BCL2 expression and decreasing caspase 3 activity (Dineva et al 2007). It is noteworthy that neither the acute nor the daily treatment altered procaspase 3 expression.…”
Section: Ctrlmentioning
confidence: 99%
“…These results are supported by previous studies that demonstrated that similar daily administrations with leptin reduce the incidence of follicular apoptosis after 7 days of leptin injection and that leptin may be involved in accelerating follicular maturation by attenuating follicular atresia through an increase in the BCL2/BAX ratio (Almog et al 2001). In addition, using different in vitro systems, other authors have found that leptin reduces apoptosis and induces cell proliferation, at least in part, by upregulating BCL2 expression (Brown & Dunmore 2007, Sirotkin & Grossmann 2007, Lam et al 2010, and that leptin may act as an anti-apoptotic factor in luteinized porcine granulosa cells by increasing BCL2 expression and decreasing caspase 3 activity (Dineva et al 2007). It is noteworthy that neither the acute nor the daily treatment altered procaspase 3 expression.…”
Section: Ctrlmentioning
confidence: 99%
“…It is known that leptin-deficient ob/ob mice exhibit the immunological changes similar to those induced by starvation, i.e., thymic atrophy and decreased maturation of T and B cells (Howard et al, 1999;Claycombe et al, 2008;Lam et al, 2010). Because serum leptin concentrations are rapidly lowered by starvation (Ahima et al, 1996), it is conceivable that leptin plays a role in the starvation-induced immunodeficiency.…”
Section: Introductionmentioning
confidence: 99%
“…MYC suppresses multiple miRNAs in lymphoma cells. Lam et al [9] found, however, that Dicer and MYC have no synergistic effect on lymphoma development, but rather the opposite. Deletion of Dicer in established B-cell lymphomas resulted in apoptosis, revealing that Dicer is required for B-cell lymphoma survival.…”
Section: B-cell Lymphomasmentioning
confidence: 96%